2021
DOI: 10.1016/j.jaccas.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Obstruction Following Surgical Repair of a Secundum Atrial Septal Defect

Abstract: Obstruction of the inferior vena cava (IVC) following surgical repair of an atrial septal defect (ASD) is a rare complication. We present the case of a patient who developed IVC obstruction following surgical repair of a large secundum ASD. The diagnostic and management approaches used to care for this patient are discussed. ( Level of Difficulty: Intermediate. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The precise anatomical understanding of the EV and its variants becomes relevant when planning procedures where this structure may interfere with a successful outcome, such as the case beautifully presented by Patel et al. ( 17 ) in this issue of JACC Case Reports .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise anatomical understanding of the EV and its variants becomes relevant when planning procedures where this structure may interfere with a successful outcome, such as the case beautifully presented by Patel et al. ( 17 ) in this issue of JACC Case Reports .…”
Section: Discussionmentioning
confidence: 99%
“…Gross anatomy studies have identified the presence of a prominent EV in up to 26% of specimens ( 14 ). A thick ER >4 mm is seen in 24% of the normal population studied using computed tomography scanning ( 15 ), and this EV variant has been cited as a cause for IVC obstruction ( 16 , 17 ) and right-to-left shunting ( 18 ) following surgical repair of atrial septal defects. This occurs when the prominent EV is mistakenly identified intraoperatively as the lower rim of an atrial septal defect and is sutured to the interatrial septum, affecting IVC flow or diverting it into the left atrium.…”
Section: Anatomical Variants Of the Ev And Its Clinical Implicationsmentioning
confidence: 99%